Deep brain stimulation for dystonia-choreoathetosis in cerebral palsy: pallidal versus thalamic stimulation - Wolf, Marc; Blahak, Christian (Parkinsonism & related disorders, 2019)
Introduction: Dystonia-choreoathetosis is common in patients with cerebral palsy, and medical treatment is mostly unsatisfactory. Deep brain stimulation (DBS) of the globus pallidus internus (GPi) has shown some eﬀect, but there is still a need to optimize treatment strategies. We aimed to assess whether the thalamic ventral intermediate nucleus (Vim) might be an alternative DBS target in dystonia-choreoathetosis. - Methods: Three patients with cerebral palsy and dystonia-choreoathetosis underwent implantation of DBS electrodes concurrently in the GPi and Vim. Final selection of stimulation site and switches during follow-up with corresponding clinical outcomes were assessed. - Results: One patient with initial GPi stimulation was switched to Vim, but likewise did not improve signiﬁcantly (BFM: pre-OP 142, GPi 140, Vim 134) and stimulation was discontinued. In one patient Vim was chosen as initial target for chronic DBS. Since clinical beneﬁt was not yet satisfying, stimulation was switched to GPi resulting in further mild clinical improvement (BFM: pre-OP 99.5, Vim 82.5, GPi 82). In one patient GPi was selected and kept on follow-up due to some therapeutic eﬀect (BFM: pre-OP 135, GPi DBS 121). - Conclusions: The GPi still represents the most convenient DBS target in patients with dystonia-choreoathetosis. Vim DBS did not show a relevant long-term advantage in everyday life in our patients. Further alternative DBS targets need to be considered in acquired dystonia.